Identification of Students' Mathematical Creative Thinking Ability in Solving Number Pattern Problems - Ivan Hartaji; Isbadar Nursit; Abdul Halim Fathani (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Improving the process of learning mathematics in the classroom requires creative thinking skills. In learning mathematics, the ability to think creatively is one of the important mathematical abilities to be mastered and developed by students. Creative thinking adds support to students so that students are more enthusiastic about solving problems. Creative thinking is the ability to explore different, quality, and task-appropriate ideas. The purpose of this study was to describe students' mathematical creative thinking abilities in the matter of number patterns for class VIII MTs Mamba'ul Ulum Pandaan. In this study the approach used is a qualitative approach, the type of qualitative used is descriptive qualitative. The data collection process was carried out at MTs Mamba'ul Ulum Pandaan. Data collection techniques were carried out in 3 ways, namely observation, tests and interviews. After the data was obtained, qualitative data analysis was then carried out which consisted of: analysis before being in the field and analysis while in the field. Analysis during the field includes data reduction, data presentation and drawing conclusions. After that, the validity of the data was tested. The results of this study indicate that students with high mathematical creative thinking abilities fulfill 4 indicators. Students with moderate creative thinking abilities meet 2 indicators, while students with low creative thinking abilities do not meet any of the predetermined indicators.